2021
DOI: 10.1021/acs.est.1c01573
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Spectroscopic Quantification of Phosphorus Transformation in Saharan Dust during Trans-Atlantic Dust Transport

Abstract: Saharan dust is an important phosphorus (P) supply to remote and oligotrophic parts of the oceans and American lowland tropical rainforests. Phosphorus speciation in aeolian dust ultimately controls the release and bioavailability of P after dust deposition, but the speciation in Saharan dust and its change during the trans-Atlantic transport remains unclear. Using P K-edge X-ray absorption near edge structure (XANES) spectroscopy, we showed that with increasing dust traveling distance from the Sahara Desert t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…The increase in P bioavailability was significant at every pH unit drop, starting from 7 to 6, 6 to 5, or 5 to 4, which is the natural pH range of most soils around the world and on the surface of plant leaves (Batjes, 1995; Gross et al, 2021). Our results agree well with previous studies which reported increased P solubility when desert dust spends times in the atmosphere and goes through atmospheric acidification processes which dissolve Ca‐P minerals, even under moderate acidic conditions (Dam et al, 2021; Herbert et al, 2018; Shi et al, 2019; Stockdale et al, 2016; Zhang et al, 2018). Overall, our data shows that a moderate drop in pH, which is common in natural soils, is sufficient to promote the dissolution of Ca‐P minerals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in P bioavailability was significant at every pH unit drop, starting from 7 to 6, 6 to 5, or 5 to 4, which is the natural pH range of most soils around the world and on the surface of plant leaves (Batjes, 1995; Gross et al, 2021). Our results agree well with previous studies which reported increased P solubility when desert dust spends times in the atmosphere and goes through atmospheric acidification processes which dissolve Ca‐P minerals, even under moderate acidic conditions (Dam et al, 2021; Herbert et al, 2018; Shi et al, 2019; Stockdale et al, 2016; Zhang et al, 2018). Overall, our data shows that a moderate drop in pH, which is common in natural soils, is sufficient to promote the dissolution of Ca‐P minerals.…”
Section: Discussionsupporting
confidence: 93%
“…For example, modification of rhizospheric pH promotes the dissolution of P bearing minerals and the exudation of organic acids such as malic acid and oxalic acid which desorb mineral bound P via exchange reactions with Ca, Fe and Al minerals (Devau et al, 2010; Hinsinger, 2001; Hinsinger et al, 2009; Lambers et al, 2019; Penn & Camberato, 2019). These processes can affect P bioavailability of desert dust since most of its P is bound to pH sensitive Ca minerals such as apatite (the major P bearing mineral in desert dust) or Fe and Al oxides (Dam et al, 2021; Gross et al, 2015; Gu et al, 2019; Hudson‐Edwards et al, 2014; Longo et al, 2014; Nenes et al, 2011; Stockdale et al, 2016; Zhang et al, 2018). Controlled laboratory studies with synthetic minerals have shown that the dissolution of Ca‐P minerals increases at pH lower than 8 while desorption of P from Fe and Al oxides will occur at moderately acidic conditions (Devau et al, 2010; Herbert et al, 2018; Penn & Camberato, 2019; Smith et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Total P, S, and typical metal­(loid)­s including arsenic (As), cadmium (Cd), copper (Cu), and Fe in the samples were determined after being digested with HNO 3 –HClO 4 . Organic P was determined using the ashing method . Available As and P were extracted with 0.5 mol/L NaHCO 3 (pH 8.5), available S was extracted with 0.016 mol/L KH 2 PO 4 , and available Cd, Cu, and Fe were extracted with a DTPA complexing solution .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Organic P was determined using the ashing method. 34 Available As and P were extracted with 0.5 mol/L NaHCO 3 (pH 8.5), 31 available S was extracted with 0.016 mol/L KH 2 PO 4 , 9 and available Cd, Cu, and Fe were extracted with a DTPA complexing solution. 21 The chemical speciation distribution of Cu and Fe in the samples was quantified with a sequential extraction procedure (Text S2).…”
Section: Methodsmentioning
confidence: 99%
“…The above results demonstrated that a strong connection existed between DOM in lakes and air pollution closely related to human activities. For instance, dust as a vector for the transport of nutrients and pollutants at the global scale could cause a shift in DOM in alpine lakes. , …”
Section: Resultsmentioning
confidence: 99%